Black Manhood in James Baldwin, Ernest J. Gaines, and August Wilson - Clark, Keith, 1963- (Book collections on Project MUSE., 2002)
Publisher's description: From Frederick Douglass to the present, the preoccupation of black writers with manhood and masculinity is a constant. Black Manhood in James Baldwin, Ernest J. Gaines, and August Wilson explores how in their own work three major African American writers contest classic portrayals of black men in earlier literature, from slave narratives through the great novels of Richard Wright and Ralph Ellison. Keith Clark examines short stories, novels, and plays by Baldwin, Gaines, and Wilson, arguing that since the 1950s the three have interrupted and radically dismantled the constricting literary depictions of black men who equate selfhood with victimization, isolation, and patriarchy. Instead, they have reimagined black men whose identity is grounded in community, camaraderie, and intimacy. Delivering original and startling insights, this book will appeal to scholars and students of African American literature.